Pemberian Core Stability Exercise Mengurangi Nyeri Punggung Bawah pada Pasien dengan Kondisi Low Back Pain Myogenic di RS Baptis Batu - Linda Amiriawati; Achmad Fariz; Retno Dewi Prisusanti; Agung Hadi Endaryanto; Angria Pradita (FORIKES, 2021)
Low back pain myogenic is discomfort in the area around the lower back is caused by weakness and imbalance of the back muscles. Core stability exercises are believed to be able to maintain the stability of the vertebral position by activating the trunk (core) muscles, diaphragm, abdominal muscles and basic muscles. This study aims to investigate the decrease in the degree of complaints of low back pain after giving core stability exercise. With a pre-post study design, one group used a numerical rating scale (NRS) measurement before and after 8 treatments for 4 weeks. A total of 20 samples in the 45-65 years age group. The results of this study indicate a median value of 5.50 on the NRS measurement before administering core stability and a median value of 3.00 on the NRS measurement after the administration of core stability indicating a Wilcoxon test significance value <0.001. The conclusion of this study shows that the provision of core stability exercise techniques is effective in reducing pain in patients with low back pain.Keywords: low back pain; core stability; numeric rating scaleABSTRAKNyeri punggung bawah myogenik adalah rasa tidak nyaman di daerah sekitar punggung bawah disebabkan oleh kelemahan dan ketidakseimbangan otot-otot punggung. Latihan core stability diyakini dapat menjaga kestabilan posisi vertebra dengan mengaktivasi otot trunk (core), diafragma, otot abdominal dan otot dasar. Penelitian ini bertujuan untuk menginvestigasi penurunan derajat keluhan nyeri punggung bawah setelah pemberian latihan core stability. Dengan desain penelitian pre-post satu kelompok menggunakan pengukuran numeric rating scale (NRS) sebelum dan sesudah 8 kali treatment selama 4 minggu. Sebanyak 20 sampel pada kelompok umur 45-65 tahun. Hasil penelitian ini menunjukkan nilai median 5.50 pada pengukuran NRS sebelum pemberian core stability dan nilai median 3.00 pada pengukuran NRS setelah pemberian core stability menunjukkan nilai signifikansi uji Wilcoxon <0,001. Kesimpulan penelitian ini menunjukkan bahwa pemberian teknik core stability exercise efektif dalam menurunkan nyeri pada penderita nyeri punggung bawah myogenik.Kata kunci: nyeri punggung bawah; core stability; numeric rating scale